Transurethral Holmium laser cystlithotripsy using 80 watt energy - Sharma, Suman (Journal of Manmohan Memorial Institute of Health Sciences, 2014)
DOI: http://dx.doi.org/10.3126/jmmihs.v1i2.9908 Journal of Manmohan Memorial Institute of Health Sciences Vol.1(2) 2013; 45-46